Platelet and coagulation factors in proliferative diabetic retinopathy. Issue 6 (June 1984) - Borsey, D Q; Prowse, C V; Gray, R S; Dawes, J; James, K; Elton, R A; Clarke, B F
Abstract : Plasma beta-thromboglobulin, platelet factor 4, fibrinogen, fibrinopeptide A, antithrombin III, factor VIII related antigen, alpha 2-macroglobulin, platelet count, and total glycosylated haemoglobin were measured in three well matched groups of subjects: non-diabetic controls, diabetics without retinopathy, and diabetics with proliferative retinopathy. beta-thromboglobulin and platelet factor 4 concentrations were significantly higher in the diabetics with retinopathy than in the controls and platelet factor 4 was also increased in the diabetics without retinopathy compared with controls. Fibrinogen concentration was raised in diabetics without retinopathy compared with controls, diabetics with retinopathy compared with controls, and diabetics with retinopathy compared with those without. Fibrinopeptide A concentration did not differ significantly between groups. Antithrombin III levels were increased in diabetics with retinopathy compared with controls, and in diabetics with retinopathy compared with those without. Factor VIII related antigen values were higher in both the diabetic groups when compared with the controls. Fibrinopeptide A concentration correlated with both beta-thromboglobulin and platelet factor 4 in each of the three groups. Haemostatic abnormalities in diabetes have been shown, although a hypercoagulable state has not been confirmed. These changes in platelet and coagulation function may be secondary to the development of microvascular disease and their role in the pathogenesis of retinopathy remains uncertain.